Ts. Dr. Norazlianie produces portable carbon membrane for hydrogen purification - Nur Hartini, Mohd Hatta (2020)
Kuantan, 29 September 2020 - The new carbon membrane producers that offer supported carbon membrane in commercial-scale quantities prove that the current market focuses more on competitive and affordable unit price.